Depression in the COVID-19 endemic era: Analysis of online self-disclosures by young South Koreans. - Seoyoung Kim; TaeYoon Aum; Dong-Gwi Lee (PLoS ONE)
Although COVID-19 has been declared endemic in South Korea, there are economic and psychosocial after-effects. One of these is the prevalence of depression. Depressed adolescents and young adults struggle with insecurity, loneliness, and lack of confidence due to the life limitations imposed during the pandemic. Young South Koreans experienced deterioration in mental health because of the recurrence of mass infections. To address professionals' concerns about the lingering effects of COVID-19 on youth mental health, we text-mined young South Koreans' online posts about depression during the pandemic and the endemic phases-from February 2020 to May 2023. We used a total of 1,740 selected posts (raw data publicly available on https://github.com/kimalexis1129/PLOS_endemic_depression.git) to explore the situational triggers, additional factors, and by-products of depression that have persisted during the endemic era. We used Latent Dirichlet allocation and Dirichlet-multinomial regression topic modeling methods in conjunction with sentiment analysis and mean comparison. The results showed that the pandemic and endemic topic models shared similarities, but emerging topics showed extended adversities such as adolescents' vulnerability to eating disorders and young adults' tendency to self-isolate. Comparisons between the levels of positive and negative affect during the pandemic and endemic eras revealed no significant changes in mood. We discussed the results in comparison with SARS and MERS precedents and from general and cultural perspectives.